EPIDEMIOLOGICAL CHARACTERISTICS OF GENDER DIFFERENCES OF SENILE AORTIC STENOSIS IN FERGANA VALLEY - Sobirjonov Islombek Tavakkaljon ugli; Khujamberdiev M.A.; Usmonova Dilorom Ne'matjonovna (Scholar Express Journals, 2024)
Longevity is a unique example of physiological aging, slow involutional changes, long-term maintenance of homeostasis and high adaptive potential. In this regard, it is of undoubted interest not only in scientific but also in applied aspects to study physiological and pathological features of long-livers from various natural-geographical, social and ecological zones. Our work is based on the analysis of the results of examination of 62 longlivers aged from 90 to 101 years, the average age is 92.29±2.40 years. The study is one-stage, selective. The analysis of the structure of morbidity of long-livers was carried out, anthropometric characteristics and clinical and laboratory data were studied.
Keywords: Aging; polymorbidity; longevity